Local and Systemic Therapies for Breast Cancer Patients: Reducing Short-term Symptoms with the Methods of Integrative Medicine - Hack, C. C.; Voiß, P.; Lange, S.; Paul, A. E.; Conrad, S.; Dobos, G. J.; Beckmann, M. W.; Kümmel, S. (Geburtshilfe und Frauenheilkunde, 2015)
With improved prognosis due to advances in the diagnosis and therapy of breast cancer, physicians and therapists now focus on aspects such as quality of life and the management of side effects from breast cancer treatment. Therapy- and disease-related side effects often reduce the patientʼs quality of life and can place a further burden on patients, with non-compliance or discontinuation of therapy a potential consequence. Study data have shown that therapy- and disease-related side effects can be reduced using the methods of integrative medicine. Reported benefits include improving patientsʼ wellbeing and quality of life, reducing stress, and improving patientsʼ mood, sleeping patterns and capacity to cope with disease. Examining the impact of integrative medicine on the side effects of cancer treatment would be beyond the scope of this review. This article therefore looks at short-term side effects of cancer treatment which are usually temporary and occur during or after local and systemic therapy. The focus is on mind-body medicine, acupuncture and classic naturopathic treatments developed by Sebastian Kneipp as complementary therapies. The latter includes hydrotherapy, phytotherapy, nutritional therapy, exercise therapy and a balanced lifestyle.
Keywords: complementary and alternative medicine; CAM; integrative medicine; breast cancer; naturopathic treatment; phytotherapy